Lipid Metabolism Reprogramming and Trastuzumab Resistance in Breast Cancer Cell Lines Overexpressing the ERBB2 Membrane Receptor - Katia Cortese; Marco Ponassi; Aldo Profumo; Gabriela Coronel Vargas; Erika Iervasi; Maria Cristina Gagliani; Grazia Bellese; Sara Tavella; Patrizio Castagnola (Membranes, 2023)
Trastuzumab (Tz), an antibody targeting ERBB2, has significantly improved the prognosis for breast cancer (BCa) patients with overexpression of the ERBB2 receptor. However, Tz resistance poses a challenge to patient outcomes. Numerous mechanisms have been suggested to contribute to Tz resistance, and this study aimed to uncover shared mechanisms in in vitro models of acquired BCa Tz resistance. Three widely used ERBB2+ BCa cell lines, adapted to grow in Tz, were examined. Despite investigating potential changes in phenotype, proliferation, and ERBB2 membrane expression in these Tz-resistant (Tz-R) cell lines compared to wild-type (wt) cells, no common alterations were discovered. Instead, high-resolution mass spectrometry analysis revealed a shared set of differentially expressed proteins (DEPs) in Tz-R versus wt cells. Bioinformatic analysis demonstrated that all three Tz-R cell models exhibited modulation of proteins associated with lipid metabolism, organophosphate biosynthesis, and macromolecule methylation. Ultrastructural examination corroborated the presence of altered lipid droplets in resistant cells. These findings strongly support the notion that intricate metabolic adaptations, including lipid metabolism, protein phosphorylation, and potentially chromatin remodeling, may contribute to Tz resistance. The detection of 10 common DEPs across all three Tz-resistant cell lines offers promising avenues for future therapeutic interventions, providing potential targets to overcome Tz resistance and potentially improve patient outcomes in ERBB2+ breast cancer.